The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/4207367
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biobased Polyurethane Foams Employing Lignin Fractionated from Microwave Liquefied Switchgrass

Abstract: Lignin samples fractionated from microwave liquefied switchgrass were applied in the preparation of semirigid polyurethane (PU) foams without purification. The objective of this study was to elucidate the influence of lignin in the PU matrix on the morphological, chemical, mechanical, and thermal properties of the PU foams. The scanning electron microscopy (SEM) images revealed that lignin with 5 and 10% content in the PU foams did not influence the cell shape and size. The foam cell size became larger by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The shoulder of -C=O may appear due to the intermolecular H bonding in polymer structure. These transitions of IR bands strongly established the synthesis of polyurethane sample [6,[16][17][18]. Other noticeable bands in IR spectra of synthesized CPUF were symmetric and antisymmetric bands of aliphatic -CH at 2933 cm -1 and 2855 cm -1 , aromatic C=C stretching band at 1645 cm -1 and 1595 cm -1 , and multiple stretching bands of ester C-O at 1064 cm -1 , 1160 cm -1 , and 1214 cm -1 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The shoulder of -C=O may appear due to the intermolecular H bonding in polymer structure. These transitions of IR bands strongly established the synthesis of polyurethane sample [6,[16][17][18]. Other noticeable bands in IR spectra of synthesized CPUF were symmetric and antisymmetric bands of aliphatic -CH at 2933 cm -1 and 2855 cm -1 , aromatic C=C stretching band at 1645 cm -1 and 1595 cm -1 , and multiple stretching bands of ester C-O at 1064 cm -1 , 1160 cm -1 , and 1214 cm -1 .…”
Section: Resultsmentioning
confidence: 63%
“…Polyurethane is an exclusive class of synthetic polymers which contains urethane link (-NHCOO). It is well known for versatile applications from cushioning to coatings due to tunable properties [6][7][8]. Polyurethane foams are extensively involved in water treatment processes, directly and indirectly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various lignocellulosic biomass types such as poplar, southern pine, bamboo, bagasse, agricultural residues, and lignin have been microwave liquefied in alcohol solvents to produce PU foams. As shown in Figure 2, under different liquefaction conditions (the mass ratio of bagasse flour and biocomponent polyhydric alcohol was 1 : 2, 1 : 3, and 1 : 4 and the temperature was 125°C and 150°C), all the synthesized PU foams were of rigid type and the foam was darker in color with the addition of the liquefied bagasse [49,60,[74][75][76][77][78][79][80]. The properties of the fabricated biobased foams from microwave-liquefied products were largely dependent on the biomass type, heating methods, and liquefaction conditions.…”
Section: Integrated Utilization Of Liquefied Liquidmentioning
confidence: 99%
“…The poor thermal stability is mainly because the molecular weight of the microwave liquefaction product of corn stover is lower than that of the conventional liquefied product, resulting in a decrease in the degree of crosslinking of the synthesized polyurethane [26]. The application of the proper amount (less than 10%) of lignin fractionated from the microwave-assisted liquefied switchgrass into the PU matrix could improve the performances of PU foams in the apparent density, mechanical strength, and thermal stability [79]. By adding 20% biopolyol from microwave-liquefied rape straw, the biofoam cell diameter decreased by 90% compared with the PU without biopolyol from rape straw and the foam cell became more International Journal of Polymer Science homogenous and finer, and the PU foams exhibited extremely low thermal conductivity and excellent mechanical strength.…”
Section: Integrated Utilization Of Liquefied Liquidmentioning
confidence: 99%
“…Catalysts were involved in most of the lignin liquefaction reactions in hydrogen donor solvents with microwave heating. The catalysts mostly used for the microwave assisted lignin liquefaction could be generally divided into homogeneous and heterogeneous catalysts [20,21,26,46,[49][50][51][52][53][54][55][56]. Several studies reported the application of homogeneous catalysts in the microwave assisted lignin liquefaction in hydrogen donor solvents, which could be generally grouped into acid/base catalysts and/or metal salts.…”
Section: Effect Of Catalystsmentioning
confidence: 99%